mRNA NFATC1 Expression in Genu Osteoarthritis with Effusion - Muhammad Reagan; Hermansyah; Rachmat Hidayat; Surya Darma; Putri Muthia (Fakultas Kedokteran Universitas Sriwijaya (Faculty of Medicine, Universitas Sriwijaya) Indonesia, 2020)
Based on a study conducted by the WHO Global Burden of Disease in 2010 stated, OA ranks11th, the cause of disability in the world, and ranks 6th in East Asia and the Asia-Pacificcountries, ranked 10th in North America, ranked 7th in Eastern Europe , and ranked 13th inWestern Europe. Pathogenesis of osteoarthritis (OA) as degenerative joint disease that was oncethought caused by a mechanical process. The prevalence, etiology, pathogenesis and progressionof OA are still not understood until now, mainly because of the many influencing factors. Thistype of research is a analytic study. It was conducted in Rheumatology Polyclinic Dr.Mohammad Hoesin Palembang from February to December 2019. Affordable researchpopulation is all genu osteoarthritis sufferers with effusion who go to Dr. RSUP MohammadHoesin Palembang as 80 samples. Comparison of NFATC1 mRNA levels in genu osteoarthritispatients with effusion shows that there is no difference in gender and history of diabetes, whereashypertension history and degree of osteoarthritis based on Lawrence Kalgren shows significantlydifferent expression of NFATC1 mRNA. Age with NFATC1 mRNA expression showed nosignificant correlation, in contrast to BMI, Stroke Test and joint effusion volume showed a weaksignificant correlation, even though the direction of the correlation was negative on Stroke Testand joint effusion volume.